(untitled) (Texas Journal of Agriculture and Biological Sciences, 2023)
This article would be discussed Phytoseiulus (Phytoseiulus persimilis Ah) Phytoseiidae is a family of phytoseids, parasitoformes are a genus of parasitoformes – a genus of parasitopharm mites – a predatory mite belonging to the family of phytoseid. It is often found in countries with hot climates. The egg is flat, whitish in color, with yellowish spots. In the month of April, when the average daily temperature reaches 12 ° C, it leaves the wintering grounds and feeds additionally for 1-2 days. The fertilized female tick oviposits eggs around the web of the spider mite or under leaves close to the root system. The larva has 3 pairs of limbs, 0.17-0.20 mm long, and yellowish in color. A one-year-old nymph, like an adult, has a pair of limbs. The body of a two-year-old nymph is larger than that of a one-year-old. The color of their body can be determined using binoculars. Females evolve in the middle of 18-24 days, and during this time they can lay 80 or 100-110 eggs. In Uzbekistan, they are common in the Tashkent, Andijan, and Samarkand regions, they are found in cotton, cherry, apple, plum, pumpkin, and other herbs